“One for All”: Functional Transfer of OMV-Mediated Polymyxin B Resistance From Salmonella enterica sv. Typhi ΔtolR and ΔdegS to Susceptible Bacteria - Marchant, Pedro; Carreño, Alexander; Vivanco, Eduardo; Silva, Andrés; Nevermann, Jan; Otero, Carolina; Araya, Eyleen; Gil, Fernando; Calderón, Iván L.; Fuentes, Juan A. (Frontiers in Microbiology, 2021)
The appearance of multi-resistant strains has contributed to reintroducing polymyxin as the last-line therapy. Although polymyxin resistance is based on bacterial envelope changes, other resistance mechanisms are being reported. Outer membrane vesicles (OMVs) are nanosized proteoliposomes secreted from the outer membrane of Gram-negative bacteria. In some bacteria, OMVs have shown to provide resistance to diverse antimicrobial agents either by sequestering and/or expelling the harmful agent from the bacterial envelope. Nevertheless, the participation of OMVs in polymyxin resistance has not yet been explored in S. Typhi, and neither OMVs derived from hypervesiculating mutants. In this work, we explored whether OMVs produced by the hypervesiculating strains Salmonella Typhi ΔrfaE (LPS synthesis), ΔtolR (bacterial envelope) and ΔdegS (misfolded proteins and σE activation) exhibit protective properties against polymyxin B. We found that the OMVs extracted from S. Typhi ΔtolR and ΔdegS protect S. Typhi WT from polymyxin B in a concentration-depending manner. By contrast, the protective effect exerted by OMVs from S. Typhi WT and S. Typhi ΔrfaE is much lower. This effect is achieved by the sequestration of polymyxin B, as assessed by the more positive Zeta potential of OMVs with polymyxin B and the diminished antibiotic's availability when coincubated with OMVs. We also found that S. Typhi ΔtolR exhibited an increased MIC of polymyxin B. Finally, we determined that S. Typhi ΔtolR and S. Typhi ΔdegS, at a lesser level, can functionally and transiently transfer the OMV-mediated polymyxin B resistance to susceptible bacteria in cocultures. This work shows that mutants in genes related to OMVs biogenesis can release vesicles with improved abilities to protect bacteria against membrane-active agents. Since mutations affecting OMV biogenesis can involve the bacterial envelope, mutants with increased resistance to membrane-acting agents that, in turn, produce protective OMVs with a high vesiculation rate (e.g., S. Typhi ΔtolR) can arise. Such mutants can functionally transfer the resistance to surrounding bacteria via OMVs, diminishing the effective concentration of the antimicrobial agent and potentially favoring the selection of spontaneous resistant strains in the environment. This phenomenon might be considered as the source for the emergence of polymyxin-resistance in an entire bacterial community.